Karyotypic architecture of Zygogramma bicolorata Pallister (Coleoptera: Chrysomelidae: Chrysomelinae) from Kurukshetra, Haryana, India - Paramjeet Kaur, (The Bioscan, 2025)
This study examined the chromosomal structure and behavior of Zygogramma bicolorata, a species belonging to the subfamily Chrysomelinae within the family Chrysomelidae. Traditional Giemsa staining was employed for morphological characterization, while C-banding was used to detect constitutive heterochromatin. Karyotype analysis revealed a diploid chromosome number of 2n = 24 and a meioformula of 11AA + Xyp. Most chromosomes were either metacentric or submetacentric, whereas the Y chromosome was acrocentric. Within the subfamily Chrysomelinae, both increases and decreases in chromosome number were observed, likely resulting from centric fission and centric fusion events, respectively. But in genus Zygogramma only increase in chromosome number suggests the involvement of Robertsian centric fission in the generation of karyotypic diversity.